Optimizing Hippocampal‐Cortical Network Modulation via Repetitive Transcranial Magnetic Stimulation: A Dose‐Finding Study Using the Continual Reassessment Method - Freedberg, Michael; Reeves, Jack A.; Toader, Andrew C.; Hermiller, Molly S.; Kim, Eunhee; Haubenberger, Dietrich; Cheung, Ying Kuen; Voss, Joel L.; Wassermann, Eric M. (Neuromodulation (Malden, Mass.), 2020)
Objective Repetitive transcranial magnetic stimulation (rTMS) can cause potentially useful changes in brain functional connectivity (FC), but the number of treatment sessions required is unknown. We applied the continual reassessment method (CRM), a Bayesian, adaptive, dose‐finding procedure to a rTMS paradigm in an attempt to answer this question. Materials and Methods The sample size was predetermined at 15 subjects and the cohort size was set with three individuals (i.e., five total cohorts). In a series of consecutive daily sessions, we delivered rTMS to the left posterior parietal cortex and measured resting‐state FC with fMRI in a predefined hippocampal network in the left hemisphere. The session number for each successive cohort was determined by the CRM algorithm. We set a response criterion of a 0.028 change in FC between the hippocampus and the parietal cortex, which was equal to the increase seen in 87.5% of participants in a previous study using five sessions. Results A ≥criterion change was observed in 9 of 15 participants. The CRM indicated that greater than four sessions are required to produce the criterion change reliably in future studies. Conclusions The CRM can be adapted for rTMS dose finding when a reliable outcome measure, such as FC, is available. The minimum effective dose needed to produce a criterion increase in FC in our hippocampal network of interest at 87.5% efficacy was estimated to be greater than four sessions. This study is the first demonstration of a Bayesian, adaptive method to explore a rTMS parameter.